2016
DOI: 10.1515/iss-2016-0004
|View full text |Cite
|
Sign up to set email alerts
|

Chances, risks and limitations of neoadjuvant therapy in surgical oncology

Abstract: Over the last decades, neoadjuvant treatment has been established as a standard of care for a variety of tumor types in visceral oncology. Neoadjuvant treatment is recommended in locally advanced esophageal and gastric cancer as well as in rectal cancer. In borderline resectable pancreatic cancer, neoadjuvant therapy is an emerging treatment concept, whereas in resectable colorectal liver metastases, neoadjuvant treatment is often used, although the evidence for improvement of survival outcomes is rather weak.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 68 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…Since its introduction in the 1950s, NAT has been used in a variety of cancers to improve surgical resectability and reduce systemic disease burden to prolong survival [ 15 ]. For patients with PDAC, it may provide a chance to complete a full treatment of multiagent chemotherapy, as many patients are too frail postoperatively to undergo scheduled adjuvant therapy [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since its introduction in the 1950s, NAT has been used in a variety of cancers to improve surgical resectability and reduce systemic disease burden to prolong survival [ 15 ]. For patients with PDAC, it may provide a chance to complete a full treatment of multiagent chemotherapy, as many patients are too frail postoperatively to undergo scheduled adjuvant therapy [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…NAT relies on clinical staging. Insufficient staging can lead to undertreatment, and over staging can lead to the overuse of NAT (53). In addition, there is another risk of overtreatment of cancers with a poor prognosis (54), see Table 4.…”
Section: Advantages and Limitations Of Natmentioning
confidence: 99%
“…Similarly, the CROSS trial demonstrated that neoadjuvant chemoradiotherapy improved median overall survival from 24 to 49.4 months vs. surgery alone [ 29 ]. However, only 25% to 30% of patients achieve a partial or complete pathological response [ 30 , 31 ], and it carries a 0.5 to 2% mortality rate [ 32 ]. Early identification of patients that respond well could improve outcomes by preventing the administration of treatment regimens that are unlikely to be effective and facilitating treatment modulation [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…By administering NAT in patients who do not respond well, surgery is delayed, which if carried out earlier may have proven more effective. The main benefits of NAT are the increased chance of complete resectability of the primary tumour, as reduced tumour mass induced by NAT decreases the area of resection required, as well as improved prognostic outcome due to the decreased incidence of nodal micrometasteses [ 32 , 35 , 36 ]. On the contrary, tumour progression during therapy can occur in those patients who do not respond well to NAT or conversely overtreatment of tumours with a favourable prognosis that are unlikely to respond to NAT.…”
Section: Introductionmentioning
confidence: 99%